AB1044 Are There Gender Specific Differences in Patient Reported Outcomes at Initiation of Golimumab Treatment in Rheumatoid Arthritis?. (10th June 2014) - Sholter, D.; Bensen, W.G.; Choquette, D.; Fortin, I.; Arendse, R.; Kelsall, J.; Sheriff, M.; Faraawi, R.; Rodrigues, J.; Zummer, M.; Dixit, S.; Starr, M.; et al.
Abstract : Background: The prevalence of rheumatoid arthritis (RA) is 2-4 times higher in women compared to men. Furthermore, RA incidence in women increases from the age of menarche peaking around menopause, while it is rare in men younger than 45 years (1). Several studies have shown that treatment outcomes are worse in women (2). Objectives: This analysis examined gender-specific differences with respect to disease parameters at initiation of the first anti-TNF agent for RA treatment in a Canadian routine clinical practice setting. Methods: BioTRAC is an ongoing, prospective registry of patients initiating treatment for RA, AS, or PsA with infliximab or golimumab as first biologics or after having been treated with a biologic for less than six months. In this analysis, data were assessed from RA patients treated with golimumab subcutaneous as a first biologic who were enrolled between 2010 and 2012. Results: 121 RA patients were included with mean (SD) disease duration of 9.3 (9.6) years. Eighty-nine patients (73.6%) were female. In the overall population, rheumatoid factor positivity was observed in 67% of patients and 17.5% were smokers, without any significant differences between genders. Patient reported disease parameters differed significantly between genders. Despite the younger age (56.6 vs. 62.0 years; P=0.051), female patients reported significantly higher pain (56.6 vs. 44.5 mm; P=0.045), patient global assessment (PtGA: 6.0 vs. 4.7 cm; P=0.034), tender joint count (10.2 vs. 6.8; P=0.022), and functional disability (HAQ-DI: 1.43 vs. 1.06; P=0.024). In addition, a statistical trend towards higher morning stiffness in female patients was observed (55.7 vs. 38.9; P=0.063). However, physician assessment of global disease activity (MDGA: 5.7 vs. 5.5; P=0.581), SJC (7.9 vs. 8.5; P=0.641), DAS28-ESR (5.3 vs. 4.7; P=0.086), CDAI (29.7 vs. 24.5; P=0.120) and SDAI (32.1 vs. 30.2; P=0.675) were statistically comparable between genders. Conclusions: Objective measures (SJC, CRP/ESR), MDGA and composite outcomes were similar for male and female patients at golimumab initiation, with the exception of TJC being higher in women. Patient reported outcomes (PROs: pain, PtGA, HAQ-DI), however, were worse at baseline for female patients at biologic treatment initiation. These findings are similar to our previous research on patients initiating anti-TNF IV therapy (3). Overall, the results may suggest gender bias in the interpretation and use of PROs during the treatment decision making process in Canadian RA patients. References: Wilder RL. J Rheumatol Suppl. 1996 Mar;44:10-2. Forslind K. et al. Ann Rheum Dis. 2007 Jan;66(1):46-52. Bensen W. et al. J Rheumatol Suppl. 2013 Jun:40:1020-1. Disclosure of Interest: D. Sholter: None declared, W. Bensen: None declared, D. Choquette: None declared, I. Fortin: None declared, R. Arendse: None declared, J. Kelsall: None declared, M. Sheriff: None declared, R. Faraawi: None declared, J. Rodrigues: None declared, M. Zummer: None declared, S. Dixit: None declared, M. Starr: None declared, E. Rampakakis: None declared, J. Sampalis: None declared, F. Nantel Employee of: Janssen Inc Canada, M. Shawi Employee of: Janssen Inc Canada, S. Otawa Employee of: Janssen Inc Canada, A. Lehman Employee of: Janssen Inc Canada DOI: 10.1136/annrheumdis-2014-eular.3979